Liver function tests values in albino wistar rats administered with isolated Nigeria Achatina achatina snail lectin - Odiegwu, Chukwujekwu Nwabueze C.; Chianella, Iva; Azubike, N. C.; Odiegwu, U. O.; Ogbuowelu, O. S. (GSC Online Press, 2021)
Achatina achatina snail specie are considered by many people in Nigeria, Ghana and other parts of West Africa to be the most prized snail for eating. In general, lectins bind to sugar moieties in cell walls or membrane, thereby change the physiology of the membrane to cause agglutination, mitosis or other biochemical changes in the cell. It has been deduced that lectins could be toxic and can as well be used as potent administrations that could be used or serve as substitutes for routine treatment or management of many disorders. Based on these, the toxicity of the Achatina achatina snail lectin in animals was investigated with a view to determining the nutritional value of the snail as food stuffs by carrying out tests to determine the blood values of Liver Function Tests (LFT) parameters in Albino Wistar Rats administered with the lectin. A total of 120 samples of the Nigeria Achatina achatina snail specie were collected, authenticated at the Zoology Department of the University of Nigeria, Nsukka and 80mls of pooled crude Lectin extract was obtained. Purifications were performed on 20mls of the crude extract in three steps viz, Ammonium sulphate precipitation and Dialysis (Partial purifications), Con A Sepharose 4B affinity Chromatography column (Complete purification). The affinity purified lectin was used for all the tests conducted in this research. The crude, partially and complete/affinity purified Lectin extracts were subjected to Haemagglutination tests. The Lectin was further assessed to determine its effects on Liver Function Tests (LFT) parameters viz, Total bilirubin (TB), Conjugate bilirubin (CB), Alkaline phosphatase (ALP), Aspartate transaminase (AST) and Alanine transaminase (ALT) as follows: A total of Thirty-five (35) male Albino Wistar Rats weighing 101-180g and aged 2-3 months obtained from the Animal house of University of Nigeria, Nsukka, were used in this research. The animals were Grouped into 5 (A-E) and allowed for 2 weeks acclimatization. Graded doses of 0.04ml, 0.05ml and 0.06ml of the Affinity purified Lectin were administered intra-peritoneally to each of the rats in Groups A-D (test groups) according to their body weights at intervals of 2 days for 1 week. Group E served as the control. Two (2) mls of blood was collected from each of the rats before and 24 hours after the last day of lectin administration for the following tests: TB, CB, ALP, AST and ALT (performed by means of Roche Cobas C111 automated chemistry analyser). The results of the research showed as follows: On complete/affinity purification, 15mls of pure sample containing only the high molecular weight lectin was obtained. The respective haemagglutination tests on the crude, partially and affinity purified Lectin showed on standardization preferential agglutinations with Blood group A type. Bar charts statistics show that there was Post lectin administration mean increase in TB, CB and AST when the Post administrations values were compared with the Pre values. The Bar charts statistics show that there was Post lectin administration mean decrease in ALP and ALT. However, the differences in the Pre and Post administration mean values of these parameters were further subjected to one way analysis of variance (ANOVA) test statistics aimed at determining whether the mean increases or decreases in these assessed parameters were statistically significant. The ANOVA statistics show that the effects of the lectin on all the assessed LFT parameters viz, TB, CB, ALP, AST and ALT were statistically insignificant (P > 0.05). The results obtained in this research has succeeded in demonstrating that the A. achatina snail lectin is non-toxic, non-carcinogenic and therefore point to its nutritive value as food stuff, hence supports the snail eating education.
Keywords: Achatina achatina; Snail lectin; Liver function tests profile